Is core bacterial community more vulnerable to environmental changes in dammed river?. Issue 1 (April 2021) - Zhu, Shijun; Wen, Chen; Xie, Shanshan; Luo, Xia
Abstract: It is well known that dam construction has a potential to impact water quality, resulting other related changes on bacterial community structure and diversity. Yet, effects of dam construction on planktonic and sediment bacterial structure are much more fragmentary. Through sampling of water and sediments along a dammed river between winter and summer, bacterial community were investigated using Illumina high-throughput sequencing. Core bacterial community, including Proteobacteria (55.29%), Firmicutes (25.29%), Bacteroidetes (17.22%), Verrucomicrobia (1.27%) and Gemmatimonadetes (0.93%), were maintained among water and sediments and between seasons. Mantel test showed the core bacterial community was less sensitive to environmental variable. However, a few of dominant microbe, such as class Alphaproteobacteria and family Sphingomonadaceae in core community were still tightly correlated with physiochemical properties according to correlation analysis. Physiochemical characteristics in water and sediment were mainly affected by season fluctuations. Changes in sediment texture has been attributed to the dam construction. This study suggests a potential to detect possible biological indicators of human and natural pressures in riverine system.